Hubungan Mata Kuliah Kependidikan Terhadap Kesiapan Mahasiswa Prodi Pendidikan Ekonomi dalam Melaksanakan PLP di Sekolah - Bayu Surindra; Tjetjep Yusuf Afandi; Zainal Arifin; Faridha Nadzirotur Rohmah Rohmah; Liafidianti Liafidianti (Universitas Nusantara PGRI Kediri, 2026)
This study aims to analyze the relationship between educational courses and the readiness of Economics Education students in implementing the School Field Introduction Program (PLP) in schools. The research method used was a quantitative approach using a correlational design on 87 Economics Education students at levels 1 to 4. The sampling technique used in this study is using the purposive sampling technique. The results of the study showed that education courses provide a positive and significant relationship to student readiness with a correlation coefficient of 0.700 which is included in the strong category. All instrument items are valid with a correlation value above 0.3 at a significance level of 0.01. PLP 1 and PLP 2 courses had the strongest relationship with an average correlation of 0.789, followed by Learning Media and ICT with an average of 0.805, and Curriculum Studies with an average of 0.768. Students show a good understanding of the theoretical aspects, but practical skills such as student behavior management and authentic assessments still need to be strengthened. The research recommends improving practicum components, microteaching simulations, and intensive collaboration with partner schools to bridge the theoretical and practical gaps in preparing prospective professional economics teachers.